Industrial link with KANEKA - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Siti Maznah, Kabeb; Noor Suhana, Adzahar (Penerbit UMP, 2010)
Gebeng, Jan 14 - FIST's Industrial Chemistry and Material Technology groups met with KANEKA (M) Sdn. Bhd. to initiate academic and research collaborations.